Effect of MMX® mesalamine coadministration on the pharmacokinetics of amoxicillin, ciprofloxacin XR, metronidazole, and sulfamethoxazole: results from four randomized clinical trials - Pierce D; Corcoran M; Martin P; Barrett K; Inglis S; Preston P; Thompson TN; Willsie SK (Dove Medical Press, 2014)
David Pierce,1 Mary Corcoran,2 Patrick Martin,2 Karen Barrett,1 Susi Inglis,1 Peter Preston,2 Thomas N Thompson,3 Sandra K Willsie3 1Shire, Basingstoke, UK; 2Shire, Wayne, PA, USA; 3PRA International, Lenexa, KS, USA Background: MMX® mesalamine is a once daily oral 5-aminosalicylic acid formulation, effective in induction and maintenance of ulcerative colitis remission. Patients on long-term mesalamine maintenance may occasionally require concomitant antibiotic treatment for unrelated infections. Aim: To evaluate the potential for pharmacokinetic interactions between MMX mesalamine and amoxicillin, ciprofloxacin extended release (XR), metronidazole, or sulfamethoxazole in four open-label, randomized, placebo-controlled, two-period crossover studies. Methods: In all four studies, healthy adults received placebo once daily or MMX mesalamine 4.8 g once daily on days 1–4 in one of two treatment sequences. In studies 1 and 2, subjects also received a single dose of amoxicillin 500 mg (N=62) or ciprofloxacin XR 500 mg (N=30) on day 4. In studies 3 and 4, subjects received metronidazole 750 mg twice daily on days 1–3 and once on day 4 (N=30); or sulfamethoxazole 800 mg/trimethoprim 160 mg twice daily on days 1–3 and once on day 4 (N=44). Results: MMX mesalamine had no significant effects on systemic exposure to amoxicillin, ciprofloxacin, or metronidazole; the 90% confidence intervals (CIs) around the geometric mean ratios (antibiotic + MMX mesalamine: antibiotic + placebo) for maximum plasma concentration (Cmax) and area under the plasma concentration–time curve (AUC) fell within the predefined equivalence range (0.80–1.25). Sulfamethoxazole exposure increased by a statistically significant amount when coadministered with MMX mesalamine; however, increased exposure (by 12% in Cmax at steady state; by 15% in AUC at steady state) was not considered clinically significant, as the 90% CIs for each point estimate fell entirely within the predefined equivalence range. Adverse events in all studies were generally mild. Conclusion: MMX mesalamine may be coadministered with amoxicillin, ciprofloxacin, metronidazole, or sulfamethoxazole, without affecting pharmacokinetics or safety of these antibiotics. ClinicalTrials.gov identifiers: NCT01442688, NCT01402947, NCT01418365, and NCT01469637. Keywords: ulcerative colitis, pharmacokinetics, safety